Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acs.jafc.1c01229
|View full text |Cite
|
Sign up to set email alerts
|

Crop Load and Plant Water Status Influence the Ripening Rate and Aroma Development in Berries of Grapevine (Vitis vinifera L.) cv. Cabernet Sauvignon

Abstract: Wine made from grapes subjected to accelerated ripening, an increasingly frequent phenomenon occurring in many wine regions due to peaks of heat and water stress, displays higher alcohol levels and lacks balance with color and flavor compounds. Herein, the rate of sugar accumulation of grapes was manipulated by varying the crop load and irrigation regime and the development of secondary metabolites was monitored by gas chromatography–mass spectrometry (GC–MS) and high-performance liquid chromatography (HPLC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Ripening delay: In order to move grape ripening back to cooler months, options are ranging from choosing higher elevation sites [49], altered trellising systems, delayed pruning, increased crop charges (where water permits), late ripening-inducing rootstocks, varieties and clones or specific interventions in canopy management [24,39,48,50,51]. Crop load management in conjunction with the irrigation regime can help to delay ripening and positively modify fruit composition [52].…”
mentioning
confidence: 99%
“…Ripening delay: In order to move grape ripening back to cooler months, options are ranging from choosing higher elevation sites [49], altered trellising systems, delayed pruning, increased crop charges (where water permits), late ripening-inducing rootstocks, varieties and clones or specific interventions in canopy management [24,39,48,50,51]. Crop load management in conjunction with the irrigation regime can help to delay ripening and positively modify fruit composition [52].…”
mentioning
confidence: 99%
“…Their concentration in wines from the GRASS treatment area was slightly higher than that of CK in 2016, while it was the opposite in 2017. Some reports showed that benzenes originating from the metabolism of amino acids in grape fruits, especially volatile phenols, were promoted by the water stress caused by crop covering, and their concentrations were further increased in the resultant wines [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The entire time series of 28 growing seasons demonstrated that yield and sugar content tend to be inversely proportional. This is expected since each plant has a limited photosynthetic capacity and as yields increase, the photoassimilates have to be further partitioned between the fruits, which tend to accumulate sugars more slowly (Parker et al, 2015;Previtali et al, 2021). Nevertheless, pairwise comparison demonstrated that annual yield and sugar content (separately for red and white grape cultivars) vary above and below their trend lines without always exhibiting the same inverse relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Crop load influences ripening. Lower vine yields tend to accelerate maturation (sugar accumulation rate) and consequently increase grape sugar content at harvest (Nuzzo & Matthews, 2006;Parker et al, 2015;Previtali et al, 2021). In addition to crop load, seasonal effects also have a considerable impact on yields and sugar accumulation (Keller, 2020).…”
Section: Introductionmentioning
confidence: 99%